PENEGAKAN HAK ANAK DALAM PROYEK-PROYEK LANJUTAN PELUCUTAN SENJATA (DISARMAMENT), DEMOBILISASI, REINTEGRASI OLEH UNICEF DAN INTERNATIONAL RESCUE COMMITTEE (IRC) BAGI TENTARA ANAK PEREMPUAN SIERRA LEONE - Damar Kusumawardani (Indonesian Association for International Relations, 2020)
Sierra Leone was one of the countries with the largest use of child soldiers during the civil war between 1991-2002. Girl child soldiers made up to 30 percent of the total child soldiers involved in the Sierra Leone civil war. The Disarmament, Demobilization and Reintegration program (DDR) which was one of the UN mandate as a post-conflict peace consolidation could only reach 506 out of a total of 6,845 child soldiers who have been disarmed. This was because the requirement for the disarmament phase was to hand in their weapon, while many girls were not equipped with weapon by their armed forces commander considering that most of them acted as cooks, house workers, and bush wives. UNICEF and IRC as international organizations then carried out further DDR projects with more gender-responsive and community-based with gender mainstreaming and inclusive citizenship policies to enforce children rights of Sierra Leonean girl soldiers who previously had not included in DDR program. This paper will discuss the enforcement of children rights of Sierra Leonean girl soldiers in the furtjer DDR projects.